The Effect of Hawthorn Extract on Coronary Flow - Kenneth P. Dood MBS; Aaron D. Frey MBS; Timothy P. Geisbuhler PhD (SAGE Publishing, 2013)
Hawthorn extract has been used for heart failure and may decrease cardiac cell injury and improve cardiac function. One proposed mechanism for hawthorn action is vasodilation. We hypothesized that hawthorn extract would increase coronary blood flow in isolated perfused rat hearts. Coronary flow was measured in nonworking perfused rat hearts (Langendorff, constant pressure) using a flow probe; data were collected electronically in real time. Hawthorn extract showed an early (30-120 seconds) vasodilation, followed by a later (3-5 minutes) decrease in coronary flow. Maximum vasodilation occurred with 240 μg/mL hawthorn extract. Hawthorn's pattern of activity was unlike that of several known vasoactive drugs. Both nitric oxide synthase inhibitors and indomethacin abolished early vasodilation, but they had no effect on the late phase decrease in flow. We suggest that a hawthorn-induced increase in nitric oxide generation leads to an increase in prostacyclin production, thus causing early phase vasodilation.